Quantification of Stretching in the Ventricular Wall and Corpus Callosum and Corticospinal Tracts in Hydrocephalus before and after Ventriculoperitoneal Shunt Operation - Hans von Holst; Xiaogai Li (Journal of Applied Mathematics)
In this study, we establish a quantitative model to define the stretching of brain tissue, especially in ventricular walls, corpus callosum (CC) and corticospinal (CS) fiber tracts, and to investigate the correlation between stretching and regional cerebral blood flow (rCBF) before and after ventriculoperitoneal shunt operations. A nonlinear image registration method was used to calculate the degree of displacement and stretching of axonal fiber tracts based on the medical images of six hydrocephalus patients. Also, the rCBF data from the literature was analyzed and correlated with the strain level quantified in the present study. The results showed substantial increased displacement and strain levels in the ventricular walls as well as in the CC and CS fiber tracts on admission. Following shunt operations the displacement as well as the strain levels reduced substantially. A linear correlation was found to exist between strain level and the rCBF. The reduction in postoperative strain levels correlated with the improvement of rCBF. All patients improved clinically except for one patient due to existing dementia. These new quantitative data provide us with new insight into the mechanical cascade of events due to tissue stretching, thereby provide us with more knowledge into understanding of the role of brain tissue and axonal stretching in some of the hydrocephalus clinical symptoms.